Ten years of solitude: Turkey and the Western Balkans require practical integration measures to bridge the hiatus in the European Union enlargement process - Andrea Despot; Dušan Reljić; Günter Seufert (Stiftung Wissenschaft und Politik (SWP), 2012)
In the wake of Croatia's EU accession in mid-2013, it is probable that the Union's enlargement process towards Turkey and the Western Balkans will initially grind to a halt, possibly for a decade or more. How can the EU safeguard nonetheless its position as the driving force behind conflict transformation in Western Balkan states, and how can it prevent European influence on Turkey, an increasingly important player on the international stage, from dwindling? It should ensure candidates' integration within as many EU policy areas as possible prior to accession, so that the stabilising and democratising effects of the EU's enlargement policy remain intact
Keywords: 320